Heat Transfer Potentiality and Flow Behavior in a Square Duct Fitted with Double-Inclined Baffles: A Numerical Analysis. (15th July 2021) - Boonloi, Amnart; Jedsadaratanachai, Withada
Abstract : Numerical analysis of heat transfer mechanisms and flow topologies for the heat exchanger square channel (HESC) installed with the double-inclined baffles (DIB) is reported. The main objective of the present research is to study the influences of DIB height to duct height (b / H = 0.05 – 0.30 ), DIB distance to duct height (P / H = 1 – 1.5 ), and flow attack angle (α = 30 °   and   45 ° ) on the flow topologies, heat transfer features, and thermal performances. The Reynolds numbers (based on the entry HESC around 100–2000) are analyzed for the present problem. The numerical models of the HESC installed with the DIB are solved with finite volume method (commercial code). The simulated results of the HESC installed with the DIB are reported in forms of flow topologies and heat transfer characteristics. The Nusselt numbers (Nu), friction factors (f ), and thermal enhancement factors (TEF) of the HESC placed with the DIB are offered. As the numerical results, it is seen that the DIB produces the vortex streams and impinging streams in all cases. The vortex streams and impinging streams disturb the thermal boundary layer on the HESC walls that is a key motive for the growth of heat transfer rate. The best TEF of the HESC installed with the DIB is about 3.87 at P / H = 1, α = 30 °, Re = 2000, and b / H = 0.15 . Additionally, the TEF contours, which help to design the HESC inserted with the DIB, are performed.